The Strategy of Indonesian Local Skin Care to Compete Global Firm in Pandemic Situation - Asmara Khairani; Muthya Islamiaty; Inggi Qariba; Atik Aprianingsih (Jurnal Perilaku dan Strategi Bisnis, 2021)
ABSTRACT Purpose- This research aims at crafting a firm's international strategy for Indonesia's local skincare firm to enter and compete with the worldwide firm using the three main strategic approaches for competing internationally from Thompson et al. (2018). This study contributes to skincare firms in Indonesia to survive globalization and win the global market. Design/methodology/approach- This research uses a literature study: adjusts the theoretical framework with the currently existing market condition and considering the firm's competitive advantage. Findings- Local skincare companies can compete with the global market with their unique products, differentiation, and innovation. According to the internal and external analysis and strategic vision, this research recommends The Aubree use the best cost provider strategy. For the local strategy, this research uses the approach of Diamond of National Competitive Advantage. For the international strategy, this study proposes that Aubree use an export strategy to enter the global market and use a multidomestic strategy to compete globally. Originality/value- COVID-19 pandemic is currently happening and impacts many industries, including the beauty industry. Authors discuss the best strategy to implement during pandemic situations; therefore, the beauty industry, especially skincare local firms, will optimize the opportunities and win the market share.